The Dilemmas of Leading Health Organizations in Complex Settings; Comment on "Dual Agency in Hospitals: What Strategies Do Managers and Physicians Apply to Reconcile Dilemmas Between Clinical and Economic Considerations?" - Ian Greener (Kerman University of Medical Sciences, 2022)
Waitzberg and colleagues' research explores hospital managers, chief physicians and other physicians in German and Israeli hospitals, making use of thematic analysis to explore what they call 'dilemmas' between the commitments to clinical needs, and their hospitals' financial sustainability. This commentary will provide a summary of the paper, into which I will embed some items I will follow-up on in my second half. The second half will then explore these items in greater depth, considering the strengths and weaknesses of the article. I then make some suggestions for future work based around the findings the authors present in terms of managerial and clinical identity, how compromises are reached in hospital settings, and how we compare different health systems.